KEEFEKTIFAN METODE OUTDOOR LEARNING PADA MATA PELAJARAN IPA TERHADAP HASIL BELAJAR KOGNITIF SISWA KELAS III SDN SEMBUNGJAMBU 01 PEKALONGAN - Muhamad Khafidh (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
The background that encourages this research one of them is when process of teaching and learning there is students pay less attention to the teacher, the students only passively listen to the teacher's explanation and the teacher still uses conventional methods, the teacher only uses talk method and only uses the blackboard media and the results of student learning still low. As a result of the low student learning outcomes it is necessary to create a problem solving model, the need for an appropriate learning system. The learning method in accordance with the material so that the subject matter can be delivered and students are able to understand what the teacher says. Then the researchers created a solution to overcome the problem of students' understanding of thematerial in order to increase student learning outcomes, the researchers apply the learning methodOutdoor Learning.This type of research uses quantitative research with Pre-Experimental Design (nondesigns) with the type of One-Group Pretest-Posttest Design. The population of this research is all third grade students of SDN Sembungjambu 01 Bojong District, Pekalongan Regency. The samples were taken 24 third grade students of SDN Sembungjambu 01 Bojong District, PekalonganRegency.The data in this study were obtained through observation, documentation, and tests.Based on the final analysis that has been done, it can be seen from the results of the posttest and pretest that shows learning with Outdoor Learning methods is better than using conventional learning.This is reinforced by the results of the calculation of the ttest of learning completeness shows that it is known that t_ (count) is greater than t_(table) (13.78> 2.069) then H_0 is rejected.So it can be concluded that H_a is accepted, it mean that there is effectiveness of the Outdoor Learning method in science subjects on the cognitive learning outcomes of third grade students of SDN Sembungjambu 01 Pekalongan.Based on the results above, it can be concluded that the Outdoor Learning method can improve the learning outcomes of Natural ResourceSciencesmaterial in the third grade students of SDN Sembungjambu 01 Pekalongan. Keywords: Effectiveness, Method Outdoor Learning, Learning outcomes.